2014
DOI: 10.1105/tpc.114.124586
|View full text |Cite
|
Sign up to set email alerts
|

A Receptor-Like Kinase Mediates Ammonium Homeostasis and Is Important for the Polar Growth of Root Hairs inArabidopsis 

Abstract: Ammonium (NH 4+ ) is both a necessary nutrient and an important signal in plants, but can be toxic in excess. Ammonium sensing and regulatory mechanisms in plant cells have not been fully elucidated. To decipher the complex network of NH 4 + signaling, we analyzed [Ca 2+ ] cyt -associated protein kinase (CAP) genes, which encode signaling components that undergo marked changes in transcription levels in response to various stressors. We demonstrated that CAP1, a tonoplast-localized receptor-like kinase, regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(116 citation statements)
references
References 83 publications
(107 reference statements)
5
104
3
Order By: Relevance
“…A more general CrRLK1L-NOX-GEF-ROP signaling module was proposed recently as a conserved system that controls cell expansion throughout the plant (Nissen et al, 2016). Another member of the CrRLK1L family, CAP1 (for cyt Ca 2+ -associated protein kinase), was found recently to regulate root hair growth by maintaining cyt Ca 2+ gradients (Bai et al, 2014). Although CAP1 is localized in the root hair vacuolar membrane, it is responsible for maintaining an alkaline cyt pH by modulating the cytoplasmic NH 4 + levels.…”
Section: Does a Ros-independent Ph-dependent Mechanism Underlie Polamentioning
confidence: 99%
See 1 more Smart Citation
“…A more general CrRLK1L-NOX-GEF-ROP signaling module was proposed recently as a conserved system that controls cell expansion throughout the plant (Nissen et al, 2016). Another member of the CrRLK1L family, CAP1 (for cyt Ca 2+ -associated protein kinase), was found recently to regulate root hair growth by maintaining cyt Ca 2+ gradients (Bai et al, 2014). Although CAP1 is localized in the root hair vacuolar membrane, it is responsible for maintaining an alkaline cyt pH by modulating the cytoplasmic NH 4 + levels.…”
Section: Does a Ros-independent Ph-dependent Mechanism Underlie Polamentioning
confidence: 99%
“…Experiments carried out in HEK293T (human embryonic kidney) cells showed that induced mutations in the EF hand domains of NOXC and in NOXH/NOXJ proteins partially or completely suppressed ROS production (Kaya et al, 2014). Ser residues that are crucial for activity have been identified as phosphorylation sites in the N-terminal regions of several NOXs, including Ser-318/Ser-322 in NOXC (Kobayashi et al, 2007;Nühse et al, 2007;Takeda et al, 2008;Sirichandra et al, 2009;Dubiella et al, 2013;Gao et al, 2014). In NOXH and NOXJ sequences, Ser-318 also is conserved and Ser-322 is replaced with a potential Thr phosphosite.…”
Section: Apo Ros Homeostasis Is Regulated By Plasma Membrane Noxs Andmentioning
confidence: 99%
“…Additionally, a new non-invasive micro-test technique (NMT) has been taken as a useful tool for real-time measuring extracellular ions or molecular activities to noninvasively acquire information about their transportation in intact samples (Bai et al, 2014). In this study, NMT was used to determine the Ca 2+ flux in the diatom for preliminary exploring the possible physiological mechanism how AHLs affected the diatom during the initial colonization process.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…To identify new modulators of ABA signaling, some ABA-responsive genes were selected from microarray data by using the AtGenExpress Visualization Tool (http://www.weigelworld.org/resources; Kilian et al, 2007), and 50 protein kinase genes that were significantly induced (more than 5-fold) by ABA were randomly selected from the ABA-responsive genes (Bai et al, 2014). T-DNA insertion mutants of these kinase genes were obtained from the Arabidopsis Biological Resource Center (Alonso et al, 2003) for genetic analysis in a root-bending assay under the application of ABA (Murphy and Taiz, 1995;Wu et al, 1996).…”
Section: Aik1 Encodes Mkkk20 and Its Mutants Are Insensitive To Aba Imentioning
confidence: 99%